The factors that influence the occupational choices of high functioning late adolescents (ages 15-19) diagnosed with cerebral palsy in Gauteng - Jagwanth, Miksha (My University, 2021)
High functioning late adolescents with Cerebral Palsy (CP) face significant barriers to their occupational participation and performance in their occupational choices. Occupational choices and occupational participation are linked to general health and wellbeing, however late adolescents with CP are being overlooked. Previous research reveals that adolescents with disabilities have fallen through the cracks and are often forgotten in research studies. The study aimed to explore the facilitators and barriers which impact on the occupational choices of high functioning late adolescents with CP within Gauteng, South Africa (SA). It has been found that minimal research has been conducted in SA surrounding this topic, with a paucity of information surrounding adolescents with disabilities within Gauteng. Twelve (12) late adolescents (ages 15-19) with CP were selected through purposive sampling, using a preselected criterion relevant to the study’s research questions. Schools were selected through convenience sampling within Gauteng, SA. Data collection occurred through semi-structured interviews based on the Occupational Performance History Interview (OPHI-II) as a primary data gathering tool. MAXQDA, a computer data analysis programme was utilised incorporating thematic analysis for interpretation. Data analysis in the Qualitative Research process was followed for the analysis and interpretation of data. Three themes emerged from this qualitative study. Theme 1 emerged as ‘being included in their life’s decisions and their occupational choices’ which related to the facilitator which influences the occupational participation and occupational choices of high functioning late adolescents with CP. Feeling not good enough (inferior) with associated family and community stigma as well as not feeling safe within their environments were two of the main barriers which impacted negatively on their occupational choices and occupational participation. This study provided additional information surrounding decreased education of stakeholders, constant marginalisation and exclusion which are experienced by adolescents with disabilities in their communities within Gauteng, SA. Future research is recommended especially in developing contexts, local and global partnerships with other researchers, therapists and members of the community whilst sharing their research findings to increase the knowledge surrounding high functioning late adolescents with CP. This study focused on late adolescents with CP; further research is needed amongst this age category as well as expanding these ages so that barriers to meeting developmentally age-appropriate milestones throughout the years can be identified as well as predict barriers that may arise in meeting future milestones. Society needs to work as a collective so that we can decrease these barriers to facilitate success in meeting these milestones appropriately, therefore providing the individual with an increased chance for success in life. International research should be culminated, and prototypes developed to decrease experienced barriers and increase facilitators that impact the occupational choices and occupational participation of adolescents with CP. Integration of multidisciplinary approaches should be encouraged, especially within universities throughout SA and globally. The significance of the study is that it will aid to the body of knowledge surrounding high functioning late adolescents with CP. The study hopes to help guide parents, families and healthcare practitioners to prepare high functioning adolescents with CP to cope with these life changes, meet their developmental milestones and decrease the barriers that they face whilst progressing through this difficult period in their life. The facilitators should be used to improve and assist with increasing meaningful activity participation, to ensure that their occupational choices and occupational participation are positive.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy, 2021